Collagen Deposition Effect of Superoxide Dismutase Corn Kernel Extract (Zea mays L.) as Skin Photoaging Treatment - Pratiwi, Mustika Endah; Barus, Andre Anusta; Boli Tobi, Claudius Hendraman (Journal of Food and Pharmaceutical Sciences, 2025)
Intensive exposure to UV-A rays can develop photoaging in human skin. To aid this condition, several potential anti-photoaging mechanisms that have been investigated can be implemented, including collagen promotion. Collagen production in the skin has been studied promoted by an enzymatic antioxidant, superoxide dismutase (SOD). Here, we found out the collagen deposition effect from SOD crude extract of corn kernel in 3T3 fibroblast cells as alternative ingredients of anti-photoaging. Soluble protein content and SOD activity assay were executed first to prop up the main test. Collagen deposition effect was measured using staining method with picric acid solution. The result showed the highest Soluble protein and SOD activity was in 100% precipitation of corn kernel SOD extract (20.91 mg/ml and 65.50% respectively). The highest collagen deposition percentage obtained was 106.7% in 100 mg/ml corn kernel SOD extract. The collagen deposition percentage obtained was not significantly different from 2.5 mg/ml ascorbic acid. Based on viewing collagen condition under a microscope, there was an improvement in collagen, which was indicated by the interconnected collagen fibers when the extract and ascorbic acid were given. The research that has been conducted concludes that corn kernel SOD extract has anti-photoaging activity through collagen deposition effect.